2005
DOI: 10.1097/01.mpg.0000153007.38363.37
|View full text |Cite
|
Sign up to set email alerts
|

Multidisciplinary Management of Surgical Disorders of the Pancreas in Childhood

Abstract: Surgery for pancreatic disorders in children is rarely required but may be necessary a) for definitive management of primary pancreatic pathology, b) to treat sequelae of acute or chronic pancreatitis and c) to treat an underlying cause of pancreatitis. There is a broad spectrum of potential pathologies. These patients are best managed by a multidisciplinary team approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 31 publications
(32 reference statements)
1
18
0
Order By: Relevance
“…10 Acute recurrent pancreatitis can occur in up to 15% to 36% of children who have acute pancreatitis. 22,23 A pseudocyst, one of the more common complications of acute pancreatitis and acute recurrent pancreatitis, is defined as "a collection of amylase-rich pancreatic fluid that lacks an epithelial lining" 19(p417) and includes nonnecrotic tissue. A more heterogeneous collection of fluid with necrotic tissue present is identified as postnecrotic collection or necrotizing pancreatitis.…”
Section: Potential Complicationsmentioning
confidence: 99%
“…10 Acute recurrent pancreatitis can occur in up to 15% to 36% of children who have acute pancreatitis. 22,23 A pseudocyst, one of the more common complications of acute pancreatitis and acute recurrent pancreatitis, is defined as "a collection of amylase-rich pancreatic fluid that lacks an epithelial lining" 19(p417) and includes nonnecrotic tissue. A more heterogeneous collection of fluid with necrotic tissue present is identified as postnecrotic collection or necrotizing pancreatitis.…”
Section: Potential Complicationsmentioning
confidence: 99%
“…Gene sequencing of the 7q35 chromosome region revealed a strong association of the (p.R122 H) mutation of the PRSS1 gene encoding cationic trypsinogen with hereditary pancreatitis (Teich et al, 2006). Developments in genetics have shown that in the majority of patients, hereditary pancreatitis is usually associated with expression of one of two specific mutations in the cationic trypsinogen PRSS1 gene, specifically R122H or N29I.…”
Section: Calcifying Chronic Pancreatitismentioning
confidence: 99%
“…In vitro the mutations increase autocatalytic conversion of trypsinogen to active trypsin and thus probably cause premature intrapancreatic trypsinogen activation in vivo. The clinical presentation is highly variable, but most affected mutation carriers have relatively mild disease (Teich et al, 2006).…”
Section: Calcifying Chronic Pancreatitismentioning
confidence: 99%
See 2 more Smart Citations